Cancer Stem Cell Markers for Urinary Carcinoma. (15th March 2022) - Xia, Pu; Liu, Da-Hua; Xu, Ze-Jun; Ren, Fu
Abstract : Cancer stem cell (CSC) refers to cancer cells with stem cell properties, that is, they have the ability of "self-renewal" and "differentiation." Cancer stem cells exist in cancer cells and are the "culprit" of cancer recurrence and metastasis. It is difficult to be found because of its small amount, and it is difficult for anticancer drugs to produce effects on it. At present, the isolation and identification of cancer stem cells from many solid tumors are still quite difficult, mainly due to the lack of specific molecular markers of cancer stem cells. In this review, cancer stem cell surface markers and functional markers in urinary system were summarized. These markers can provide molecular targets for cancer therapy.